Turnover Intention: Career Development and Compensation Approach, and Job Satisfaction as an Intervening Variable - Harini, Sri; Narimawati, Umi; Hadi, Silviana Marwa; Yuningsih, Erni (Universitas Dharma Wacana, 2023)
This study aims to determine the effect of career development and compensation variables on turnover intention with job satisfaction as an intervening variable for employees of Hotel Leuweung Geledegan Ecolodge Bogor. This sampling uses a saturated sample technique or non-probability sampling, with a total of 50 permanent employees except the General Manager. Measurement in the questionnaire using a 5-item Likert scale. The data analysis technique in this study used the IBM SPSS v25 software application with the path analysis method. The analysis used in this study includes a validity test, reliability test, normality test, coefficient of determination test, F test, t-test, and Sobel test to determine the mediating effect. The results in this study indicate that 1) Career development and compensation simultaneously have effect and significant on job satisfaction, 2) Career development has a positive and significant effect on job satisfaction, 3) Compensation has a positive and significant effect on job satisfaction, 4) Career development, compensation and job satisfaction simultaneously and significantly on turnover intention, 5) career development has a negative and significant effect on turnover intention, 6) compensation has a negative and significant effect on turnover intention, 7) job satisfaction has a negative and significant effect on turnover intention, 8) career development has no indirect effect on turnover intention through job satisfaction, 9) compensation does not have an indirect effect on turnover intention through job satisfaction.